Sosialisasi Pencegahan Bullying Melalui Kelompok Literasi Sekolah UPT SPF SMPN 55 Barombong Makassar - Bahrul Amsal; Ulfa Utami Mappe; Mario Mario; Riri Amandaria; Sunaniah Sunaniah; Muhammad Aksha Wahdah (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
The PKM program is carried out by providing socialization to participants regarding the understanding and prevention of bullying in the school environment with the aim of (1) to increase knowledge about bullying based on school literacy groups, (2) participants can properly implement efforts to prevent bullying through literacy groups in the process of activities at school. , and (3) participants can disseminate or disseminate knowledge about the dangers of bullying in the school environment through a literacy group approach. The main target audience for PKM Program activities are school supervisors, school principals, school teachers, and students at UPT SPF SMPN 55 Barombong Makassar. The results obtained in the PKM program activities are increased knowledge and concepts of bullying prevention based on school literacy groups, increased understanding regarding the flow of prevention and reporting if bullying occurs at school, and PKM program participants can implement their own attitudes so as not to become perpetrators of bullying in the school environment and community environment.. The outcomes of PKM activities are (1) increased knowledge of participants regarding activity materials, (2) scientific articles published at national seminars, and (3) publication of PKM implementation on online media.